DESKRIPSI PENGETAHUAN DAN KEPATUHAN REMAJA PUTRI DALAM MENGKONSUMSI TABLET TAMBAH DARAH (Penelitian crossectional di POSYANDU Remaja Kecamatan Ngadiluwih) (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Adolescent girls are very at risk for anemia and require special attention related to health because the need for iron in adolescent girls increases, this occurs due to growth and the arrival of menstruation. The general aim of this study was to find out the description of the knowledge and compliance of young women in consuming iron supplement tablets at the Youth Posyandu in Badal Pandean Village, Ngadiluwih District, Kediri Regency. The research method used is a descriptive survey with a cross sectional approach. The data collection tool used a questionnaire to 35 young women. The sampling technique is simple random sampling. Descriptive data analysis by describing knowledge about anemia and adherence of young women in consuming iron tablets in the frequency distribution table. The results of the study from 35 respondents the majority of knowledge about anemia was sufficient as many as 15 respondents (42.9%) and the majority of consumption of iron supplement tablets was non-compliant as many as 19 respondents (54.3%). In this era of increasingly rapid digital development, this can be an alternative to increase youth knowledge about anemia, by utilizing mobile phones owned by young women, the village of Badal Pandean and the Wonorejo Health Center can work together to make a special web that contains health education, especially about anemia, videos can also be made. education through tik tok, Instagram and other social media. Furthermore, teenagers can download the CERIA application (Preventing Anemia Adolescents Indonesia) from the Ministry of Health to remind them to take iron tablets by setting a schedule for 1 day a week to drink blood tablets in order to minimize non-adherence to taking blood tablets.